The Effectiveness of Using Related Words and Unrelated Words in Teaching Vocabulary for Seventh Graders - Anggi Mutia Marsaulina; Adnan Latief; Emalia Iragiliati (Jurnal Pendidikan Humaniora, 2015)
Abstract: This present study is aimed at examining whether there is a significant difference in the vocabulary mastery of students who are taught using semantically related words and those who are taught using unrelated words. Quasi Experimental Research is used with Posttest Only Design involving 54 students from two classes. A vocabulary test is constructed as a main instrument. Data of students’ score are analyzed by using Independent T-test. Findings reveal that semantically related words method has positive effects on students’ retention. It is recommended that English teachers implement semantically related words. They should also consider the materials is beneficial for students. Key Words: semantically related words, unrelated words, teaching vocabularyAbstrak: Penelitian ini ini bertujuan untuk menguji keberadaan perbedaan signifikan dalam penguasaan kosakata siswa yang diajar menggunakan semantically related words dan siswa yang diajarkan menggunakan semantically unrelated words. Kuasi Experimental Research digunakan dengan Posttest Only Design dan melibatkan 54 siswa dari dua kelas. Sebuah tes kosakata dibangun sebagai instrumen utama. Data skor siswa dianalisis dengan menggunakan Independent T-test. Temuan menunjukkan bahwa semantically related words memiliki efek positif pada retensi siswa. Disarankan agar guru bahasa Inggris menerapkan semantically related words. Mereka juga harus mempertimbangkan materi-materi yang bermanfaat bagi siswa.Kata kunci: semantically related words, unrelated words, pengajaran kosakata